Development of Thematic Concept Understanding Assessment In Class V Science Learning Content. - Yusri Adi; Nurhasanah Bakhtiar; Rian Vebrianto; Adisti Yuliastrin (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2023)
Problems that are often faced by educators in measuring the level of understanding of students' concepts are questions that are made to have a low cognitive level and short answers which make the questions unable to properly measure the students' understanding. This study is useful in describing how the feasibility of a concept understanding assessment instrument is. The research design in this study is Research and Development based on the Borg & Gall model by only carrying out 5 steps due to several reasons. The subject of this research is an instrument for assessing the ability to understand concepts. The results of the analysis of the 12 assessment questions are feasible to use because they have a validity value of 0.56 with a "enough" category and a reliability value of 0.72 with a "enough" category and can be said to be a valid research instrument. And because there are 3 questions that have a negative significant value (-) then questions number 2, 10 and 12 are omitted so that this instrument is more valid.